Le tambour comme image et comme langage dans la poésie caribéenne francophone et dans Tambour-Babel (1996) d’Ernest Pépin - Kwaterko, Józef (Ponti/Ponts, 2021)
This article elaborates on the identity building function of popular music in Haiti and the Antilles in order to define the specific role of drums and drummers (the “masters tambouyè”) in Tambour-Babel by Ernest Pépin. In this novel, drums and their music provide not only a recurrent leitmotiv, but also a language that resonates with African reminiscences and echoes the creole spoken in the Antilles. We will also see how the rhythmic structure of the text contributes to the sonic (musical) poetics of the novel, as well as to its multilinguism, which reflects the cultural identity of the Antilles but also faces new issues and propose new values adapted to various intercultural contexts. The myth of Babel acquires thus a ‘post-Babelian’ positive value as a reflection of the diversity inscribed in the cultural landscape of the Caribbean.